Characterization of Divalent Metal Soaps of Cannabis Sativa Seed Oil - YETGİN, Senem; EGBUCHUNAM, Theresa O.; OKİEİMEN, Felix; GÖKKUŞ, Kutalmış; GÜNEY, Kerim (Gazi University Journal of Science, 2023)
In this study, the structural characteristics and thermal degradation behaviour of barium, calcium and zinc soaps of hemp seed oil prepared using the metathesis method are reported. Scanning electron micrographs of the metal soaps showed similar plate-like microstructures and are indicative of an orderly packed particulate structure. The bands at 1509, 1539 and 1543 cm-1 in the FTIR spectra showed the association of the carboxylate ion with Ba, Ca and Zn ions respectively The thermal decomposition consisted of one single step on the weight loss – temperature curves located around 250 – 450 oC for all the divalent metal soaps at the various heating rates and the observed loss in weight which occurred before 200 oC was minimal (< 10%). The average values of the apparent activation energy for the thermal process were 18.73, 13.77 and 8.48 kJ/mol for Zn-HSO, Ca-HSO and Ba-HSO respectively.
Keywords: Engineering; Mühendislik; Cannabis sativa; Metal soaps; Thermal degradation; Activation energy; Morphology